ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL PRODUKSI KARET DI PT. SOCFINDO AEK PAMINGKE - erlina mayasari siregar; Imsar Imsar; Fauzi Arif Lubis (Universitas Dharmawangsa, 2023)
ABSTRACTThis study aims to determine the effect of land area, number of trees and climate change (rainfall) on rubber production at PT. Socfindo Aek Pamingke. The method used is quantitative with secondary data at PT. Socfindo Aek Pamingke. The sample for this research is the number of months of production from 2016-2020, namely 60 research samples. Data analysis technique using SPSS 23.00. The results of this study indicate that based on the t test on land area tcount > ttable 111.675 > 2.00324 which means Ha1 is accepted, meaning that land area has a significant effect on rubber production at PT. Socfindo Aek Pamingke. The t test on the number of trees t count < t table is 0.565 < 2.00324 which means that Ha2 is rejected, meaning that the number of trees does not have a significant effect on rubber production. The results of the t-test for climate change (rainfall) tcount > ttable -3.271 > -2.00324 means that Ha3 is accepted, meaning that climate change (rainfall) has a significant effect on rubber production at PT. Socfindo Aek Pamingke. The results of the F test show Fstatistics > Ftable 4.925 > 2.77 so that it can be concluded that Ha4 is accepted, or in other words land area, number of trees and climate change (simultaneous) affect rubber production at PT . Socfindo Aek Pamingke, where the probability value is 0.004 <0.050.Keywords: Land Area, Number of Trees, Climate Change, Production Results.